Chlorophyll a concentration of phytoplankton during a cruise of the 46th Japanese Antarctic Research Expedition in 2004-2005 - Otsuki, Akihisa S.; Hirawake, Toru; Fukuchi, Mitsuo (National Institute of Polar Research, 2006)
P(論文) departmental bulletin paper